Dithiothreitol-assisted polysulfide reduction in the interlayer of lithium–sulfur batteries: a first-principles study. Issue 30 (14th May 2019) - Liu, Jiaqin; Li, Mo; Zhang, Xiaofei; Zhang, Qi; Yan, Jian; Wu, Yucheng
Abstract : The reaction mechanism of dithiothreitol-assisted polysulfide reduction in lithium–sulfur batteries was clarified based on systematic theoretical study. Abstract : Lithium–sulfur batteries are attracting more and more attention due to the high specific energy density and specific capacity density. The severe "shuttle effect" during the charge/discharge cycle causes significant performance degradation, and has become a great challenge for the practical application of rechargeable lithium–sulfur batteries. The biological reductant dithiothreitol (DTT) in the interlayer of lithium–sulfur batteries could reduce the shuttle effect by chemically cutting the polysulfide. The biocatalysts of molecular scission provide a gentle and innovative way to address the problems in lithium–sulfur batteries. Understanding the specific working principle of DTT would serve to expand the application of reducing agents in lithium–sulfur battery systems. A systematic theoretical study has been performed on the DTT-assisted polysulfide reduction. The steps for DTT to reduce the polysulfide chains, including the intermediate product of each reduction step ( i.e. cleavage site of polysulfides) were clarified. The difference between the reduction of long chain and short chain polysulfides and the modification method of DTT to promote the reduction kinetics were also unraveled. It is hoped that our study could provide mechanistic insights into the DTT promoted performance of Li–S batteries and give inspiration for biological reagent expansion.